2022
DOI: 10.1002/elsa.202100174
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol electro‐reforming in alkaline electrolysis cells for the simultaneous production of value‐added chemicals and pure hydrogen – Mini‐review

Abstract: Glycerol is a cheap, non‐toxic, and renewable by‐product of the rapid expansion of biodiesel and soap producers around the world. Glycerol electroforming is a method of oxidizing glycerol into valuable chemicals of interest to the pharmaceutical, cosmetics, polymer, and food industries. One of the technologies that have been studied over the past decades is to couple glycerol oxidation with the production of pure hydrogen in an electrolysis cell (so‐called electrolyzer), which has shown the advantage of consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…4b). 165 Consequently, electroreforming of solid waste derivatives offers the additional benefit of valuable chemicals at the anode paired with cathodic hydrogen generation, which endows it with energy-saving, value-addition, and cost-effectiveness advantages compared to water electrolysis for high-purity hydrogen production.…”
Section: Comprehensive Evaluation Of Electroreforming Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…4b). 165 Consequently, electroreforming of solid waste derivatives offers the additional benefit of valuable chemicals at the anode paired with cathodic hydrogen generation, which endows it with energy-saving, value-addition, and cost-effectiveness advantages compared to water electrolysis for high-purity hydrogen production.…”
Section: Comprehensive Evaluation Of Electroreforming Technologymentioning
confidence: 99%
“…, respectively, where n B , D r H f , and D r G f indicate the stoichiometric number, standard enthalpy of formation, and standard Gibbs free energy of formation, respectively. 154,165 multi-electron transfer as well as production of various chemicals (Fig. 4c).…”
mentioning
confidence: 99%
“…The synthesis of C3 products is of great interest due to their relatively high value. For example, glyceric acid has a market price of $ 126 per kg in 2022, [16] being more than a hundred times more valuable than formic acid ($ 0.4–$ 1.0 per kg in 2022 [17,18] ) and provides a wide range of applications, especially in the field of medicine, in the synthesis of amino acids or the treatment of skin diseases [19,20] …”
Section: Introductionmentioning
confidence: 99%
“…For example, glyceric acid has a market price of $ 126 per kg in 2022, [16] being more than a hundred times more valuable than formic acid ($ 0.4-$ 1.0 per kg in 2022 [17,18] ) and provides a wide range of applications, especially in the field of medicine, in the synthesis of amino acids or the treatment of skin diseases. [19,20] To enable the synthesis of C3 products via GOR, CÀ C cleavage must be avoided, and to achieve this, different strategies were employed to protect the glycerol molecule. [13,21] For example, Huang et al found that adding borate ions to the alcohol-containing electrolyte allowed the coordination with glycerol, converting glycerol into a secondary alcohol and facilitating the synthesis of dihydroxyacetone with enhanced faradaic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the oxidative upgrading of glycerol to various chemicals (Chart ) has been investigated extensively. In particular, electrochemical approaches are promising since not only does direct electro-oxidation of glycerol promise to be a greener and more sustainable route for the production of these chemicals but electrochemical approaches also have the advantage of pairing glycerol oxidation as the anode reaction with other useful cathode reactions such as hydrogen evolution or CO 2 reduction. Many chemicals can be obtained from glycerol oxidation, which either maintain the C3 backbone (Chart , blue) or are C2 products resulting from one oxidative C–C cleavage reaction (Chart , purple) or are C1 products resulting from two oxidative C–C cleavage reactions (Chart , green). Generally, formic acid (FA) is found to be the major product from glycerol electrolysis, especially when non-noble-metal-based electrocatalysts are used. , While FA is an important industrial chemical that finds use as an animal feed preservative and in the leather and tanning and textiles industries, many of the C2 and C3 products are more valuable (i.e., higher market price) with established or emerging markets. , For example, glyceric acid (GLA), one of the C3 products, can be used to produce biobased polymers, surfactants, and skin care products. ,, Thus, there is a need to rationally control the extent of C–C cleavage during glycerol electro-oxidation in order to target specific compounds.…”
Section: Introductionmentioning
confidence: 99%